School quality and teacher characteristics as correlates of students’ learning outcomes in history in Rivers State (2017)
Students 'performances in senior secondary school history in recent time have not been impressive based on the reports from public examiners. The subject is not offered by many students and is almost going into extinct as important as it is to individual citizen and the country as a whole. The extent to which school quality and teachers' characteristics correlate with students learning outcome in history in Rivers State was investigated. The study is a descriptive design of survey type. Multistage sampling technique was employed and data were collected from 30 history teachers and 200 SSS II history students from 20 SSS schools in Rivers State. Five research questions and four validated instruments guided the study with reliability coefficients of 0.78 for SQQ;0.67for TCCRS; 0.72 for CIS and 0.56for HAT respectively. Data were analysed using descriptive and inferential statistics. Results indicated a significant relationship between school quality and students' learning outcome in history (r —. 494); revealed a significant relationship between teacher characteristics and students' learning outcome in history (r = .415); both variables jointly explain 25% of the variance observed in students' learning outcome in history and it was statistically significant at F (df =2, 228) = 5.712, p < 0.05. It was observed that there were positive relationships among school quality, teacher characteristics and students' learning outcome in history. Government should provide trainings for teachers through seminars/workshops in order to develop their knowledge, practices and attitude that are neededfor maximum students'learning outcome in history.